Policy benchmarking and tracking the agricultural policy environment in Nigeria - Sanyal, Prabuddha; Babu, Suresh Chandra (International Food Policy Research Institute, 2010)
Although the Nigerian economy depends significantly on the oil sector, agriculture remains its mainstay. Agriculture contributed 42 percent of Nigeria's gross domestic product (GDP) in 2008 (National Bureau of Statistics). Agriculture is the second largest export earner after crude oil and the largest employer of rural labor; thus, the sector ranks as a key contributor to wealth creation and poverty reduction. However, despite having grown at an annual rate of 6.8 percent from 2002 to 2006—2.8 percentage points higher than the sector's annual growth between 1997 and 2001—food security remains a major concern due to the subsistence nature of the country's agriculture (Nwafor 2008).